Electoral Systems in Divided Societies - V. Lal, Brij; Larmour, Peter (Canberra ANU Press, 2012)
Elections can increase tension in ethnically divided societies, like Fiji. The way constituencies are drawn and votes counted can also affect the result. First-past-the post can deliver lopsided results, while proportional representation may give excessive influence to small, fringe parties. Fiji$1 (Bs Constitution Review Commission believed a system of alternative voting in ethnically mixed constituencies would encourage politicians, and parties, to take into account the interests of other ethnic groups. This book assesses their recommendations, looks at alternatives, and considers how they might work in Fiji.s
English
Keywords: Elections & referenda; politics; elections; fiji; Fijians; First-past-the-post voting; Instant-runoff voting; Mauritius; Melanesia; Multiracial; Proportional representation